Auto-ecology of Guadua aff. paraguayana (Poaceae) Autoecologia de Guadua aff. paraguayana Döll (Poaceae) - Franklin Galvão; Cátia Regina Augustin; Gustavo Ribas Curcio; Bruno Polli Domanowski; Carina Kozera; Alison Tadeu Sawczuk; Annete Bonnet (Pesquisa Florestal Brasileira, 2010)
Bamboos are agents of natural remediation, but its outbreak in an already established landscape may have an intense repercussion, completely changing the flora of the area. A study to determine the effects of the presence of Guadua aff. paraguayana Döll (Poaceae) found in the last remnants of the riparian forest in the areas of permanent preservation of the Wildlife Refuge of Rio Tibagi - a conservation unit in process of stablishment on the Parana’s second plateau, has been developed. This aggressive and opportunistic woody species develops vigorous tussocks in consequence of its pachymorph rhizome system a form of “short neck”; and gets established only on the higher portions of the degraded flood plain. The tussocks have an average size of 2.79 meters, with 11 stems/ m². The shooting season lasts, on average, four months and occurs between spring and summer. The culms have an average length of 13 m, with an increment of 18 cm/day during the stretch period. The average diameter at breast height is 4.25 cm. The tussocks are formed from only one stem that expands from extremely robust sprouts. When it shoots up over the canopy and receives direct sunlight, it forms a kind of braided branches and leaves capable of hardly increase the shade levels and suppress the established vegetation, changing the local succession patterns. doi: 10.4336/2009.pfb.58.05 Bambus são agentes de remediação natural, mas sua irrupção numa paisagem já estabelecida pode ter repercussão intensa, alterando completamente a florística da área. Para estabelecer os efeitos da presença de Guadua aff. paraguayana Döll (Poaceae) – um dos pouco conhecidos bambus maciços do planeta – sobre os últimos remanescentes da Floresta Ombrófila Mista Aluvial, nas áreas de preservação permanente do Refúgio de Vida Silvestre do Rio Tibagi, unidade de conservação em processo de criação no Segundo Planalto Paranaense, está-se desenvolvendo o estudo de sua autoecologia. Esta espécie lenhosa, agressiva e oportunista, forma touceiras vigorosas devido ao desenvolvimento de rizomas do tipo paquimorfo de pescoço curto e se estabelece apenas nas feições mais projetadas da planície aluvial degradada. As touceiras têm área média de 2,79 m², com 11 colmos/m². A fase de brotação dura, em média, quatro meses e ocorre entre a primavera e o verão. Os colmos têm comprimento médio de 13 m, com incremento de 18 cm/dia no período de estiramento. O diâmetro médio a 1,30 m é de 4,25 cm.As touceiras são formadas por apenas um indivíduo que se expande a partir de brotações extremamente robustas. Quando superam o dossel e recebem radiação direta, formam uma espécie de trançado de ramos e folhas capaz de aumentar fortemente o sombreamento e suprimir a vegetação instalada, modificando os padrões de sucessão local. doi: 10.4336/2009.pfb.58.05